A Rare Case of Dislodged Chemoport Catheter Entrapment in the Pulmonary Artery - Sanjay Shrestha; Naveen Kumar Pandey; Lokesh Shekher Jaiswal; Achyut Gyawali; Brijesh Pandey; Rajan Thapa; Jeet Prasad Ghimire; Bhuwan Thapa; Pawan Chaurasia (Case Reports in Vascular Medicine)
Implantable subcutaneous chemoports are routinely employed for delivering chemotherapy in oncology. Spontaneous catheter dislodgement and embolization of the catheters are rare complications of the procedure. Herein, we report our experience with a patient presenting with spontaneous dislodgement and migration of the catheter to the pulmonary artery. The patient having familial adenomatous polyposis with adenocarcinoma of the right colon underwent total proctocolectomy and had placement of the chemoport through the internal jugular vein for adjuvant FOLFOX chemotherapy. The entrapped catheter was successfully managed by percutaneous retrieval by an interventional cardiologist.